Case report: Extending the spectrum of clinical and molecular findings in FOXC1 haploinsufficiency syndrome - Garza Flores, Alexandra; Nordgren, Ida; Pettersson, Maria; Dias-Santagata, Dora; Nilsson, Daniel; Hammarsjö, Anna; Lindstrand, Anna; Batkovskyte, Dominyka; Wiggs, Janey; Walton, David S.; Goldenberg, Paula; Eisfeldt, Jesper; et al. (Frontiers in Genetics, 2023)
FOXC1 is a ubiquitously expressed forkhead transcription factor that plays a critical role during early development. Germline pathogenic variants in FOXC1 are associated with anterior segment dysgenesis and Axenfeld-Rieger syndrome (ARS, #602482), an autosomal dominant condition with ophthalmologic anterior segment abnormalities, high risk for glaucoma and extraocular findings including distinctive facial features, as well as dental, skeletal, audiologic, and cardiac anomalies. De Hauwere syndrome is an ultrarare condition previously associated with 6p microdeletions and characterized by anterior segment dysgenesis, joint instability, short stature, hydrocephalus, and skeletal abnormalities. Here, we report clinical findings of two unrelated adult females with FOXC1 haploinsufficiency who have ARS and skeletal abnormalities. Final molecular diagnoses of both patients were achieved using genome sequencing. Patient 1 had a complex rearrangement involving a 4.9 kB deletion including FOXC1 coding region (Hg19;chr6:1,609,721-1,614,709), as well as a 7 MB inversion (Hg19;chr6:1,614,710-8,676,899) and a second deletion of 7.1 kb (Hg19;chr6:8,676,900-8,684,071). Patient 2 had a heterozygous single nucleotide deletion, resulting in a frameshift and a premature stop codon FOXC1 (NM_001453.3): c.467del, p.(Pro156Argfs*25). Both individuals had moderate short stature, skeletal abnormalities, anterior segment dysgenesis, glaucoma, joint laxity, pes planovalgus, dental anomalies, hydrocephalus, distinctive facial features, and normal intelligence. Skeletal surveys revealed dolichospondyly, epiphyseal hypoplasia of femoral and humeral heads, dolichocephaly with frontal bossing and gracile long bones. We conclude that haploinsufficiency of FOXC1 causes ARS and a broad spectrum of symptoms with variable expressivity that at its most severe end also includes a phenotype overlapping with De Hauwere syndrome.